ANALISIS SUBSEKTOR DAN KOMODITAS UNGGULAN PERTANIAN DI KABUPATEN ASMAT - Nata Nasution (AGRICOLA, 2013)
This study aimed to identify leading subsectors and leading agricultural commodities in the regency of Asmat. The method used was descriptively-analytical and explorative method. The data used was time series data namely a secondary data of PDRB of Asmat regency at constant prices in 2000 and the value data of production of agricultural commodities during the period of 5 years (2006-2010). The analysis showed that forestry and fishery subsectors were leading agricultural subsectors in Asmat regency. The leading Agricultural commodities were marine fisheries, inland fisheries, logs, sawn timbers, sago, Kemedangan and Gambir.